The Development Impact of Paiton Steam Power Plant (PLTU) on Socio-Economic Life of Binor Village of Paiton District of Probolinggo Regency 1990-2016 - Yunita Wulandari; Sumarno Sumarno; Sumardi Sumardi (History Education, University of Jember, 2018)
The construction of steam power plant Paiton in 1982 in Paiton Sub-district Probolinggo District is a powerhouse established by the government with the help of foreign capital or private companies aimed at fulfilling the electricity needs in Java and Bali. The construction of steam power plant Paiton is the beginning of a change of equilibrium in a Binor village system. The purpose of this research is to analyze the impact caused by the development construction of steam power plant Paiton. The impact construction of steam power plant Paiton development has positive and negative impacts on the socio-economic life of the Binor Village community, such as impacts on people's livelihoods, education, regional infrastructure and social interaction which will lead to significant changes to the life of the Binor Village community before and after the construction of steam power plant Paiton.Keywords: The impact of PLTU Paiton, Socio-economic life